MEASURING SUSTAINABILITY PERFORMANCE IN UNIVERSITY: IS IT POSSIBLE TO IMPLEMENT SUSTAINABILITY ACCOUNTING IN PUBLIC SECTOR ORGANIZATION? - Kurniawan, Putu Sukma (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2020)
This study aims to identify the ability of non-business organizations to implement the concept of sustainability accounting and to measure the organization’s sustainability performance. The object of this study is higher education institutions (public universities). This study used a qualitative paradigm with data collection techniques and using the document analysis method. The data used is the university’s sustainability report and relevant documents. The methods used to analyze sustainability performance is the GASU method and the STARS System. The results of this study found that public university organizations can apply the concept of sustainability accounting and have a very high capability to implement the concept of sustainability accounting. This study also identified the challenges in the implementation process of sustainability accounting in public sector organizations, particularly in higher education institutions.